Analisis Emosi Akademik Sains dalam Pembelajaran Fisika dan Dampaknya terhadap Prestasi Mahasiswa - Siti Fatimah; Umi Mahmudah; Moh. Muslih; Anik Maghfiroh (Kappa Journal, 2021)
This study aims to analyze the science academic emotions of undergraduate students on physics learning especially e-learning during the COVID-19 pandemic. This research is a descriptive study using a qualitative approach. The subjects in the study were 119 PGSD students in the second semester. Then, this study uses several instruments, namely questionnaires, tests, and portfolio sheets. The results of the analysis show several important findings, namely 1) undergraduate students have good enough academic emotions, 2) positive science academic emotions have an impact on student academic achievement, and 3) 80.25% of students enjoy online physics learning and tend to have better levels of self-confidence.